Analysis of Constraints Affecting the Allocation of 3 Kg LPG Gas to Base (Case Study of PT. Sintora Putra Gasindo) - Wahyu Andriansyah Naibaho; Wahyu Syarvina (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study was conducted aiming to find out what are the obstacles or problems that often or often occur in the allocation of 3 KG LPG gas to the base at PT. SINTORA PUTRA GASINDO. , company finances as well as cooperation within the company with gas agents who contract with the company. In this study, the analysis method of observation interviews and focused discussion was used (Focus Group Discussion). Mr. Muhammad Ichan Pratama as the main director of the company PT. SINTORA PUTRA GASINDO, then we make observations going into the field in the distribution of DO gas which is distributed according to the contract to find out what fraud has been committed, both the base party and the employees who work in the company. PT. SINTO RA PUTRA GASINDO. There is also the use of this research to improve the company's work system, increase the production system or the allocation of 3KG LPG gas to the base so that there is no contract termination from the base to the company due to allocations that are not in accordance with the contract. which is quite a big impact from the constraints that occur in the allocation of 3kg LPG Gas.